Ecosystem processes of prairie streams and the impact of anthropogenic alteration on stream ecological integrity - Winders, Kyle (Kansas State University, 2010)
North America has lost more than 95% of the original tallgrass prairie because of heavy land conversion, making prairie streams some of the most endangered habitats in North America. In order to effectively manage aquatic systems and improve biotic integrity of prairie streams research is needed that assesses the ecosystem characteristics of natural systems and evaluates the influence of anthropogenic alteration. We described the ecosystem characteristics of six ephemeral headwater streams draining tallgrass prairie within the Osage Plains of southwest Missouri. NO-3-N among all sites ranged from 1.56-91.36 μg L-1, NH+4-N ranged from 5.27-228.23 μg L-1, soluble reactive phosphorus ranged from below detection (1.0 μg L-1) to 41.22 μg L-1, TN ranged from 113.82-882.89 μg L-1, and TP ranged from 8.18-158.5 μg L-1during baseflow conditions. TN:TP molar ratios ranged from 22:1 to 53:1 indicating possible P was limiting relative to N in some streams. TSS during baseflow conditions ranged from 0.27-31.80 mg L-1. Autotrophic and heterotrophic comparisons of our study sites and reference sites classified our study streams as oligo-, meso-, and eu-autotrophic (N= 1, 4, and 1, respectively) and oligo-, meso-, and eu-heterotrophic (N= 4, 1, and 1, respectively). This study suggests that good water quality and moderate heterotrophic condition, with greater GPP resulting from an open canopy, are common conditions of tallgrass prairie streams. We also investigated interactions between land use/land cover, discharge rate, hydrologic alteration, and in-stream total suspended solids concentration in 23 Kansas- Missouri streams. Most streams had break points in the TSS loading rates at discharge rates exceeded <25% of days. Our estimates showed that 88% of the total annual TSS load occurred during the 11% of days with the greatest discharge rates. Buffered streams with greater percentages of grass and/or forest riparian areas had lower breakpoint values (indicating greater discharge rates were required to transport solid particles) and lower regression intercepts, which correlated to lesser TSS concentrations relative to unbuffered streams during high discharge days. In addition, grass buffered streams had smaller flood peaks and slower rise rates and forest buffered streams had less frequent floods, which lead to less total TSS transport.
Keywords: stream; ecosystem; nutrients; solids; metabolism; Biology, Limnology (0793)